Scaling Out the Next Generation of Seasonal Climate Forecasts in Africa - Hansen, James; Grossi, Amanda; Trzaska, Sylwia; Dinku, Tufa; Beathgen, Walter; Ali, Abdou (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
AICCRA is supporting African National Meteorological Services (NMS) and Regional Climate Centres to implement Next Generation (NextGen) seasonal and sub-seasonal climate forecast systems and an improved online Flexible Forecast presentation. This brief describes the NextGen forecast system and the transformative presentation of these forecasts using an interactive web interface (Flexible Forecast Maproom), summarizes AICCRA training and support to scale out these forecast tools, and introduces a workshop process developed to equip farmers to take advantage of the Next Generation of seasonal forecasts and the Flexible Forecast Maproom.